Health public crisis impact on non-life insurance: The case of COVID-19 - Costa, M.; Gonçalves, R.; Lopes da Costa, R.; Pereira, L.; Dias, Á. (International Journal of Electronic Healthcare, 2022)
The insurance industry plays a crucial role in developing a country's economy, thus becoming one of the main focuses when studying the possible impacts of the current public health crisis. Accordingly, the main objective of this study is to investigate the COVID-19 impact on non-life insurance profitability of the Portuguese insurance sector. This study also intends to assess the explaining factors of insurance companies' profitability on the period between 2004/2020. The methodology implemented was a multiple linear regression, using a panel data model with random effects. The sample consists of a total of 238 observations from 14 non-life insurers over 17 years. The results revealed that COVID-19 positively impacted the profitability of the insurance companies presented. However, this impact was only significant on the return on assets. Furthermore, the results showed an inverse and meaningful relationship between the profitability ratios and the variables leverage and loss ratio.